A new species of Cyperus (Cyperaceae) from Brazil - Verloove, Filip; Tucker, Gordon (Phytotaxa, 2017)
Cyperus bampsii is described as a species new to science. It was collected in 1976 in a single locality near Belterra in Pará, Brazil. The species most likely belongs to section Haspani and, based on morphology and leaf anatomy, its closest relatives probably are C. haspan and C. tenuispica. The new species is described and copiously illustrated and its conservation status is assessed.